Peningkatan Keterampilan Ilmiah Peserta Didik dalam Pembelajaran Fisika Melalui Penerapan Pendekatan STEM dan E-Learning - Wisnu Wibowo, I Gusti Agung (Journal of Education Action Research, 2018)
This action research aimed to improve student’s scientific skills through implementation STEM and e-learning in physics learning. This research was conducted from 4 to 26 September 2018 and involving 27 students XI MIPA3 class of SMA Negeri Bali Mandara academic year 2018/2019.  This research consist of two learning cycles which each cycle has four stages: planning, action, observation, and reflection. Student’s scientific skills is the score achieved by the student after did some scientific activities in the class and observed by using student’s scientific skills assessment sheet. The result said that the score of each student’s scientific skill exceeded the research success criteria. On first learning cycles, there were 66% of the student’s scientific skill in the excellent category, 33% were in good category, and 11% were in enough category. Moreover, on second learning cycle, there were 44% in excellent category and 56% were in good category. The students also give a positive response to the implementation STEM and e-learning in physics learning.